2022
DOI: 10.1002/art.42091
|View full text |Cite
|
Sign up to set email alerts
|

B Cell–Specific Deletion of CR6‐Interacting Factor 1 Drives Lupus‐like Autoimmunity by Activation of Interleukin‐17, Interleukin‐6, and Pathogenic Follicular Helper T Cells in a Mouse Model

Abstract: Objective CR6‐interacting factor 1 (CRIF1) is a nuclear transcriptional regulator and a mitochondrial inner membrane protein; however, its functions in B lymphocytes have been poorly defined. This study was undertaken to investigate the effects of CRIF1 on B cell metabolic regulation, cell function, and autoimmune diseases. Methods Using mice with B cell–specific deletion of CRIF1 (Crif1ΔCD19 mice), we assessed the relevance of CRIF1 function for lupus disease parameters, including anti–double‐stranded DNA (an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…IL-17 can sustain LN both through recruitment of T cells to the kidneys, and by activating B cells to secrete autoantibodies. Previous studies on patients with LN showed abnormal levels of IL-17A both in serum and urine; importantly, serum IL-17A levels heralded major kidney damage in patients with class IV or V glomerulonephritis [10,26,[33][34][35][36], in keeping with our data.…”
Section: Discussionsupporting
confidence: 91%
“…IL-17 can sustain LN both through recruitment of T cells to the kidneys, and by activating B cells to secrete autoantibodies. Previous studies on patients with LN showed abnormal levels of IL-17A both in serum and urine; importantly, serum IL-17A levels heralded major kidney damage in patients with class IV or V glomerulonephritis [10,26,[33][34][35][36], in keeping with our data.…”
Section: Discussionsupporting
confidence: 91%
“…Instead of DC, we focused on the TSLP contribution on Th differentiation through B cell activation because immunofluorescence revealed a colocalization of TSLPR with B cells. More importantly, B cells was also required for Tfh response, as B cells could induce Bcl-6 expression in CD4+ T cells to induce and sustain Tfh differentiation [36][37][38][39][40]. We observed an induction of Tfh by TSLP activated-B cells.…”
Section: Discussionmentioning
confidence: 65%
“…The transcription factor CR6-interacting factor 1 (CRIF1) is a multifunctional protein expressed in the nucleus and cytoplasm that regulates cell cycle and growth by regulating the expression of nerve growth factor IB, androgen receptor, STAT3 and others, and is also essential for mitochondrial function. The deletion of CRIF1 in B cells impairs mitochondrial oxidative function, increases STAT3 phosphorylation levels, expresses more ICOSL and intercellular adhesion molecule (ICAM) related to T-B cell interaction, and up-regulates the expression of Tfh cells characteristic genes such as signaling lymphocytic activation molecule family member 5 ( SLAMF5 ), IFNG and C-X-C chemokine receptor 3 ( CXCR3 ), thereby increasing the frequency of Tfh cells [ 85 ]. B cells expressing PD-L1 and PD-L2 and T cells expressing PD-1 regulate the production of long-lived plasma cells and memory B cells through T-B cell interactions [ 76 ].…”
Section: Tfh Cells Migration and Maturation Stagementioning
confidence: 99%